Taxonomic revision of the Pteris cadieri complex (Pteridaceae) - Chao, Yi-Shan; Liu, Ho-Yih; Chiou, Wen-Liang (Phytotaxa, 2015)
The Pteris cadieri complex is widely distributed in South and East Asia. Due to tremendous morphological variation within and between taxa, previous taxonomic treatments have been plagued with an element of uncertainty. In this study, the morphological characteristics, along with data from previous studies on reproductive modes, cytology, and genotypes, are integrated to clarify and delineate each taxon. Nine taxa are recognized in the Pteris cadieri complex: three original species (P. cadieri, P. hainanensis and P. grevilleana), one reinstated name (P. dimorpha, synonymized under P. cadieri), two new species (P. incurvata sp. nov. and P. perplexa sp. nov.), two new varieties (P. dimorpha var. prolongata var. nov., and P. dimorpha var. metagrevilleana var. nov.), and a forma (P. grevilleana f. ornata stat. nov.). The lectotypes of P. cadieri, P. dimorpha, P. grevilleana, and P. hainanensis are designated. Each taxon is described in detail. A key is provided to facilitate the identification of all taxa.